2011
DOI: 10.1094/mpmi-01-11-0013
|View full text |Cite
|
Sign up to set email alerts
|

IPD3 Controls the Formation of Nitrogen-Fixing Symbiosomes in Pea and Medicago Spp.

Abstract: A successful nitrogen-fixing symbiosis requires the accommodation of rhizobial bacteria as new organelle-like structures, called symbiosomes, inside the cells of their legume hosts. Two legume mutants that are most strongly impaired in their ability to form symbiosomes are sym1/TE7 in Medicago truncatula and sym33 in Pisum sativum. We have cloned both MtSYM1 and PsSYM33 and show that both encode the recently identified interacting protein of DMI3 (IPD3), an ortholog of Lotus japonicus (Lotus) CYCLOPS. IPD3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 61 publications
4
99
0
8
Order By: Relevance
“…The late symbiotic event of nodule cell infection is tightly coupled to nodulation, rendering its specific analysis difficult. A genetic link between nodulation/IT formation and nodule cell infection was also evidenced on the plant side as two genes of the Nod factor signaling pathway, the leucine-richrepeat-containing receptor kinase DMI2 and the calcium-and calmodulin-dependent kinase DMI3 interacting protein IPD3, were shown to be required for symbiosome formation (Capoen et al, 2005;Limpens et al, 2005;Ovchinnikova et al, 2011). Our findings on the bacterial side provide new clues on nodulation-intracellular infection relationships by pointing to a common control for bacterial invasion at the early nodulation/root hair infection and the late nodule cell entry levels ( Figure 3b).…”
Section: Discussionmentioning
confidence: 95%
“…The late symbiotic event of nodule cell infection is tightly coupled to nodulation, rendering its specific analysis difficult. A genetic link between nodulation/IT formation and nodule cell infection was also evidenced on the plant side as two genes of the Nod factor signaling pathway, the leucine-richrepeat-containing receptor kinase DMI2 and the calcium-and calmodulin-dependent kinase DMI3 interacting protein IPD3, were shown to be required for symbiosome formation (Capoen et al, 2005;Limpens et al, 2005;Ovchinnikova et al, 2011). Our findings on the bacterial side provide new clues on nodulation-intracellular infection relationships by pointing to a common control for bacterial invasion at the early nodulation/root hair infection and the late nodule cell entry levels ( Figure 3b).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in nodules, this common signaling pathway is also essential for the release of the rhizobia from infection threads (symbiosome formation), but not for infection thread formation. This result has been demonstrated for the receptor-like kinase SymRK, the calcium-and calmodulin-dependent kinase, as well as its interacting partner (IPD3) (15)(16)(17)(18)(19)(20). It is currently not known whether this common signaling pathway is activated by Nod-factor receptors in legume nodules.…”
mentioning
confidence: 90%
“…2C). To further support that medicago type-A RR genes are targets of the cytokinin phosphorelay pathway, we isolated RNA from medicago roots transformed with the gain-of-function MtCRE1 construct (35S:MtCRE1* [L267F]), which causes spontaneous nodule formation (Ovchinnikova et al, 2011). Quantitative reverse transcriptase (RT)-PCR on root RNA showed that, of all type-A RR genes, MtRR9 was most strongly induced and also that MtRR4, MtRR5, MtRR8, and MtRR11 were activated (Fig.…”
Section: And B)mentioning
confidence: 99%
“…The MtRR9 RNAi target sequence was cloned into the DsRed modified gateway vector pK7GWIWG2(II) driven by the CaMV35S promoter as described by Limpens et al (2005). 35S:MtCRE1*[L267F] was used as described by Ovchinnikova et al (2011).…”
Section: Vectors and Constructsmentioning
confidence: 99%
See 1 more Smart Citation